Lactobacillus plantarum and molasses alter dynamic chemical composition, microbial community, and aerobic stability of mixed (amaranth and rice straw) silage. (10th March 2021) - Mu, L; Xie, Z; Hu, L; Chen, G; Zhang, Z
Abstract: BACKGROUND: The objective was to determine how molasses and Lactobacillus plantarum affect chemical composition, fermentation quality, aerobic stability, and the microbial community of an ensiled mixture of amaranth ( Amaranthus hypochondriaus, AF) and rice straw. Treatments were control (C, no addition), L. plantarum (L; 2 × 10 5  cfu g −1 fresh weight), molasses (M; 40 g kg −1 fresh matter), and their combination (LM). All treatments were ensiled for 1, 3, 5, 7, and 30 days. RESULTS: All additives improved fermentation quality with greater lactic acid (LA), acetic acid, and lower pH than C silage over the ensiling period. The LM silage combination optimized fermentability, manifested as greater LA contents and a more rapid pH reduction during the first 7 days of ensiling than L or M silages. After 30 days of ensiling, inoculant L. plantarum increased Lactobacillus abundance and reduced bacterial diversity and Enterobacteriaceae abundance compared with silage treated with molasses. Molasses addition reduced the relative concentration of structural carbohydrates (neutral and acid detergent fiber, and hemicellulose) after 30 days of ensiling. Finally, there was spoilage after 2 days and 4 days of aerobic exposure in C and LM silages respectively, whereas L silage had not spoiled after 4 days. CONCLUSIONS: Although the combination of L. plantarum and molasses further optimized fermentation characteristics, L silage had better aerobic stability. © 2021 Society of Chemical Industry.